STUDI EMPIRIS ALAT PERAGA PENERIMA FREKUENSI RADIO GRF-3300 - Deddy Susilo; Budihardja Murtianta; Nathanael Adharta Livendra Murtianta (Jurnal Edukasi Elektro, 2021)
ABSTRACT:In a wireless communication system, the transmitter and receiver are basic components that have a role in the telecommunications system. The receiving system serves to receive an information signal. The basic structure of a radio frequency receiver system, namely: antenna - low pass filter - low noise amplifier (LNA) - mixer - phase lock loop (PLL) - demodulator - audio output. This article describes an empirical study of the GRF-3300 Receiver RF Circuit Training System by presenting the results of system testing which are very easy to understand, including the workings and functions of the receiver system props and the basic modules used in the receiving system, so that it can be used help electrical engineering students, especially telecommunications engineering majors. From the test results, the RF Circuit Training System GRF-3300 receiver training kit produces a Total Harmonic Distortion test value of around 5% when an input signal of 1Vrms is given.ABSTRAK:Pada sistem komunikasi nirkabel, pemancar dan penerima merupakan komponen mendasar yang berperan dalam sistem telekomunikasi. Sistem penerima berfungsi untuk menerima suatu sinyal informasi. Struktur dasar sistem penerima frekuensi radio yaitu: antena – low pass filter – low noise amplifier (LNA) – mixer – phase lock loop (PLL) – demodulator – audio output. Dalam artikel ini menjelaskan tentang studi empiris Receiver RF Circuit Training System GRF-3300 dengan hasil pengujian yang mudah dimengerti, meliputi cara kerja dan fungsi pada alat peraga sistem penerima serta modul-modul struktur dasar yang digunakan dalam sistem penerima, sehingga dapat membantu mahasiwa teknik elektro khususnya jurusan teknik telekomunikasi. Dari hasil pengujian, alat peraga penerima RF Circuit Training System GRF-3300 menghasilkan nilai THD sekitar 5% pada sinyal masukan sebesar 1Vrms.